Extremely late-onset pulmonary metastasis from uterine PEComa - Ascione, Andrea; Martignoni, Guido; d’Amati, Giulia; Della Rocca, Carlo; Graziano, Paolo; Pernazza, Angelina (Pathologica - Journal of the Italian Society of Anatomic Pathology and Diagnostic Cytopathology, 2022)
A 79-year-old woman underwent surgical resection of a peripheral, solitary, pulmonary lesion that was diagnosed as malignant PEComa. Her clinical history was positive for uterine leiomyosarcoma, excised 20 years before. Re-evaluation of the primary uterine lesion led to the final diagnosis of lung metastasis from uterine PEComa. While long latency between primary tumour and metastasis is a known and characteristic feature of PEComas, a 20-year interval is unprecedented in the literature.